Treatment of an Indolent T‐Cell Lymphoma of the Gastrointestinal Tract Harboring STAT3::JAK2 With Jakafi (Ruxolitinib) With Significant Clinical Improvements - Xi Cao; Carolyn Mulroney; Huan‐You Wang (eJHaem)
ABSTRACT Introduction Indolent T‐cell lymphoma of the gastrointestinal tract (ITCL‐GI) is a rare primary T‐cell lymphoma from the gastrointestinal (GI) tract, there has been no documented successful treatment at the present time. Results A CD4(+)/CD8(−) ITCL‐GI with STAT3::JAK2 fusion was treated with Jakafi (Ruxolitinib), which resulted in significant clinical improvements. Conclusion Next generation sequencing is highly recommended for any new diagnosis of CD4(+)/CD8(−) ITCL‐GI in order to detect if STAT3::JAK2 can be found in order to treat the patient with JAK2 inhibitor such as Jakafi (Ruxolitinib). Clinical trial registration The authors have confirmed clinical trial registration is not needed for this submission.